Soft polyurethane foam
The introduction of urea aggregates in soft polyurethane foam, formed through a specific reaction involving diphenylmethane diisocyanate and a polyol component, addresses the challenges of durability and vibration absorption in automotive seat cushions, achieving enhanced mechanical properties and cost-effectiveness.
Patent Information
- Application Number
- JP2020169514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-10-07
AI Technical Summary
Conventional soft polyurethane foams for automotive seat cushions face challenges in achieving high durability, vibration absorption, and cost-effectiveness while maintaining low density and rebound elastic modulus.
The development of a soft polyurethane foam containing urea aggregates with a specific volume average particle diameter and area ratio, formed through a reaction involving diphenylmethane diisocyanate, a polyol component with oxyethylene units, and a modified polyisocyanate, which enhances the foam's mechanical properties and durability.
This approach results in a soft polyurethane foam with improved vibration absorption, high durability, and reduced cost, even at low densities, while maintaining desirable rebound elastic modulus and hysteresis loss rates.
Smart Images

Figure 0007647054000003 
Figure 0007647054000004 
Figure 0007647054000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a flexible polyurethane foam. [Background technology]
[0002] Conventionally, flexible polyurethane foams for automobile seat cushions (hereinafter, also referred to as flexible foams) are required to have high durability from the viewpoint of safety so that the driver's viewpoint does not change much due to a decrease in thickness even during long rides. On the other hand, in recent seat cushions, the foam's resilience modulus is required to be low in order to reduce vibrations transmitted from the road surface, and the foam density is required to be as low as possible from the viewpoint of cost reduction. However, it is known that these reductions in resilience and density significantly deteriorate the durability of the foam, and there has been a demand for the establishment of technology that achieves both durability, ride comfort, and cost-effectiveness at the same time.
[0003] As a means for solving these problems, Patent Document 1 discloses a method of reacting unmodified diphenylmethane diisocyanate (hereinafter also referred to as MDI) containing 81 to 100% of MDI and 40 to 60% of 2,2'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate in diphenylmethane diisocyanate with a polyol composition containing a polyether polyol containing at least 60 mass% of oxyethylene groups having an average nominal hydroxyl functionality of 2 to 6 and an average equivalent weight of 200 to 600. However, in this method, other active hydrogen group-containing compounds including water and the polyol having the oxyethylene unit react with the isocyanate in competition with each other, and as a result, the reaction of the terminal hydroxyl group of the polyol having the oxyethylene unit is not completed, and it is considered that the urea aggregates in the flexible polyurethane foam are not appropriately present, and therefore, a sufficient effect of reducing the hysteresis loss rate cannot be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2000 / 008083 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention is 50 kg / m 3 The object of the present invention is to provide a flexible foam having high vibration absorption properties and high durability even in the following low density range. [Means for solving the problem]
[0006] The present invention was discovered as a result of extensive investigations aimed at solving the above-mentioned problems.
[0007] That is, the present invention includes the following embodiments (1) to (5).
[0008] (1) A flexible polyurethane foam containing urea aggregates, characterized in that the volume average particle diameter of the urea aggregates is 0.32 to 0.72 μm, and the area ratio of the urea aggregates per unit area of a cross section of the flexible polyurethane foam is 6% to 15%.
[0009] (2) The flexible polyurethane foam according to the above (1), characterized in that it uses, as isocyanate components, a reaction product of diphenylmethane diisocyanate (A) with a polyol component (hereinafter also referred to as polyol component) (B) containing 30 mass% or more of oxyethylene units, and a modified polyisocyanate (C) containing polyphenylene polymethylene polyisocyanate (hereinafter also referred to as polymeric MDI).
[0010] (3) The flexible polyurethane foam according to the above (2), wherein the polyol component (B) has a number average molecular weight of 500 to 10,000.
[0011] (4) The flexible polyurethane foam according to the above (2) or (3), wherein the average functionality of the polyol component (B) is 1.7 to 4.3.
[0012] (5) The flexible polyurethane foam according to any one of the above (2) to (4), wherein the modified polyisocyanate (C) has an isocyanate content of 28.1 to 32.4 mass %.
[0013] (6) The apparent density of the flexible polyurethane foam is 50 kg / m 3 The 25% compression hardness of the skinned foam test specimen is 100 to 400N / 314cm 2 The flexible polyurethane foam according to any one of (1) to (5) above, characterized in that the range is: rebound resilience is 70% or less; hysteresis loss is 30% or less; dry heat compression set is 4% or less; and wet heat compression set is 8% or less. Effect of the Invention
[0014] The flexible polyurethane foam of the present invention has a compressibility of 50 kg / m 3 It is possible to provide a flexible polyurethane foam having high vibration absorption properties and high durability even in a low density region of less than 1000 g / m2. [Brief description of the drawings]
[0015] [Figure 1] 1 is an image of a 20 μm square of the sample obtained in Example 4 taken by a scanning probe microscope. [Diagram 2] 1 is an image of a 20 μm square of the sample obtained in Comparative Example 4 taken by a scanning probe microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The flexible polyurethane foam of the present invention is characterized in that it contains urea aggregates, the volume average particle diameter of the urea aggregates being 0.32 to 0.72 μm, and the area ratio of the urea aggregates per unit area of the cross section of the flexible polyurethane foam being 6% to 15%.
[0017] First, the urea aggregate contained in the flexible polyurethane foam of the present invention will be described. It is considered that the urea aggregate is formed by agglomeration of urea groups mainly generated by the reaction of isocyanate groups with water. It is considered that the urea aggregate has a suitable hydrophilicity and is generated in a well-balanced manner by always having an appropriate amount of polyoxyethylene units derived from the polyol component (B) contained in the modified polyisocyanate (C) present near the isocyanate groups.
[0018] This balance can be achieved by using the various raw materials described below.
[0019] The volume average particle size of the urea aggregate in the present invention is 0.32 to 0.72 μm, preferably 0.32 to 0.64 μm, and more preferably 0.32 to 0.52 μm. The area ratio of the urea aggregate per unit area of the cross section of the foam is 6% to 15%, and preferably 7% to 11%. By setting the volume average particle size and area ratio of the urea aggregate within the above ranges, a flexible polyurethane foam having good hysteresis loss rate, rebound resilience, and durability can be obtained.
[0020] Next, a preferred embodiment for obtaining the urea aggregate will be described.
[0021] The MDI (A) of the present invention is one of the isocyanate components for obtaining the modified polyisocyanate (C), and contains two benzene rings and two isocyanate groups.
[0022] MDI includes 2,2'-diphenylmethane diisocyanate (hereinafter referred to as 2,2'-MDI), 2,4'-diphenylmethane diisocyanate (hereinafter referred to as 2,4'-MDI), and 4,4'-diphenylmethane diisocyanate (hereinafter referred to as 4,4'-MDI), and the total mass of 2,2'-MDI and 2,4'-MDI relative to the total mass of MDI is called the isomer content.
[0023] In the present invention, the amount of MDI (A) and the isomer content are determined based on the target MDI content and isomer content in the modified polyisocyanate (C).
[0024] The polyol component (B) preferably contains polyoxyethylene units in an amount of 30% by mass or more, and more preferably 45% by mass or more.
[0025] As the polyol component (B), any known polyol can be used as long as it satisfies the above conditions. Examples of such polyols include those obtained by adding alkylene oxides such as ethylene oxide and propylene oxide, and cyclic ethers such as tetrahydrofuran to low-molecular-weight polyols, low-molecular-weight polyamines, and low-molecular-weight aminoalcohols having a number average molecular weight of less than 700 as initiators. Examples of the initiator include water, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, 2,2-diethyl-1,3-propanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-n-hexadecane-1,2-ethylene glycol, 2-n-eicosane-1,2-ethylene glycol, 2-n-octacosane-1,2-ethylene glycol, and the like. Examples of the low molecular weight polyols include 1,2-ethylene glycol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, ethylene oxide or propylene oxide adducts of bisphenol A, hydrogenated bisphenol A, 3-hydroxy-2,2-dimethylpropyl-3-hydroxy-2,2-dimethylpropionate, trimethylolpropane, glycerin, and pentaerythritol; low molecular weight amines such as aniline, ethylenediamine, propylenediamine, toluenediamine, metaphenylenediamine, diphenylmethanediamine, and xylylenediamine; and low molecular weight amino alcohols such as monoethanolamine, diethanolamine, triethanolamine, and N-methyldiethanolamine.
[0026] The average functionality of such a polyol component (B) is preferably from 1.7 to 4.3, and more preferably from 1.7 to 3.3.
[0027] The number average molecular weight of the polyol component (B) is preferably 500-10,000, and more preferably 500-8,500.
[0028] The modified polyisocyanate (C) contains the reaction product of the above-mentioned MDI (A) and the polyol component (B), and polymeric MDI.
[0029] In obtaining the modified polyisocyanate (C), the ratio of each component, MDI, polymeric MDI, and polyol component (B), can be determined so that the MDI content, isomer content, and NCO content are set to the desired values. There is no particular restriction on the ratio of each component, so long as each set value is within the following range.
[0030] The MDI content in the total of the MDI content in MDI (A) before reaction with polyol component (B) and the MDI content in the polymeric MDI is preferably 65 to 90 mass %, more preferably 70 to 85 mass %.
[0031] The isomer content is preferably 10 to 50 mass%, more preferably 20 to 45 mass%, in terms of the sum of the isomer content of MDI (A) before reaction with polyol component (B) and the isomer content of the polymeric MDI.
[0032] The isocyanate content of the modified polyisocyanate (C) is preferably 28.1 to 32.4 mass%, more preferably 28.3 to 32.0 mass%. By setting the MDI content, isomer content, and isocyanate content within the above ranges, a urea aggregate that satisfies each characteristic can be suitably obtained.
[0033] The synthesis method for obtaining the modified polyisocyanate (C) is not particularly limited, and examples of applicable methods include a method of reacting the entire amount of MDI (A) with the polyol component (B), and a method of reacting a part of the MDI (A) with the polyol component (B) and then mixing the remainder of the MDI (A) and polymeric MDI.
[0034] Next, the polyol (D) to be reacted with the modified polyisocyanate (C) to obtain a flexible polyurethane foam will be described.
[0035] The polyol (D) is not particularly limited, and any known polyol used in molding flexible polyurethane foams can be used without particular limitation, but one mainly composed of a polyether polyol having a hydroxyl value of 20 to 40 mg KOH / g and an average functionality of 2 to 4 is preferred.
[0036] As such a polyol (D), for example, those exemplified as the polyol component (B) can be used. Among them, those having a polyoxypropylene structure as the main chain and having ethylene oxide added to the molecular terminal are preferred.
[0037] In addition, for the purpose of adjusting the hardness of the resulting flexible polyurethane foam, a polymer polyol produced by polymerizing a vinyl monomer in a polyol by a normal method can be used in combination. Such a polymer polyol can be one obtained by polymerizing a vinyl monomer in a polyether polyol similar to the polyol (D) in the presence of a radical initiator and stably dispersing it. In addition, examples of the vinyl monomer include acrylonitrile, styrene, vinylidene chloride, hydroxyalkyl, methacrylate, and alkyl methacrylate, and among these, acrylonitrile and styrene are preferred. Specific examples of such polymer polyols include EL-910 and EL-923 manufactured by AGC, and FA-728R manufactured by Sanyo Chemical Industries, Ltd.
[0038] In obtaining the flexible polyurethane foam of the present invention, a catalyst, a crosslinking agent, a foam stabilizer, a blowing agent, etc. may be appropriately used.
[0039] As the catalyst, various known urethane catalysts and trimerization catalysts can be used. Representative examples include tertiary amines such as triethylamine, tripropylamine, tributylamine, N-methylmorpholine, N-ethylmorpholine, dimethylbenzylamine, N,N,N',N'-tetramethylhexamethylenediamine, N,N,N',N',N''-pentamethyldiethylenetriamine, triethylenediamine, bis-(2-dimethylaminoethyl)ether, 1,8-diaza-bicyclo[5.4.0]undecene-7, dimethylethanolamine, N-trioxyethylene-N,N-dimethylamine, N,N-dimethyl-N-hexylamine, etc. Examples of the catalyst include reactive tertiary amines such as sanolamine or organic acid salts thereof, imidazole compounds such as 1-methimidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2,4-dimethylimidazole, and 1-butyl-2-methylimidazole, organometallic compounds such as stannous octoate, dibutyltin dilaurate, and zinc naphthenate, 2,4,6-tris(dimethylaminomethyl)phenol, 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine, potassium acetate, and potassium 2-ethylhexanoate. The type and amount of the catalyst may be any catalyst that can realize an appropriate closed cell rate and production cycle of the foam cells, and need not be particularly specified, but the preferred amount is 0.1 to 5 parts by mass relative to the polyol in terms of foam odor and the like.
[0040] In the present invention, an alkanolamine-based crosslinking agent such as diethanolamine or triethanolamine can be added for the purpose of improving molding stability and adjusting foam hardness. The amount of the crosslinking agent added is preferably 5 parts by mass or less per 100 parts by mass of polyol (D). Adding more crosslinking agent than necessary may cause strong closed cell foaming or may deteriorate mechanical strength due to increased crosslink density.
[0041] As the foam stabilizer, known organic silicon surfactants and the like can be used, and examples thereof include SZ-1327, SZ-1325, SZ-1336, and SZ-3601 manufactured by Dow Corning Toray Co., Ltd., Y-10366, L-5309, and L-3639LF2 manufactured by Momentive Corporation, B-8724LF2 and B-8715LF2 manufactured by Evonik Co., Ltd., and F-122 manufactured by Shin-Etsu Chemical Co., Ltd. The amount of these foam stabilizers to be added is preferably 0.1 to 3 parts by mass per 100 parts by mass of the polyol (G).
[0042] The foaming agent is preferably water, and city water can be used. By using water, carbon dioxide gas is generated by the reaction between the isocyanate group and water, and foaming can be performed. The amount of water added is preferably 2 to 10 parts by mass per 100 parts by mass of the polyol (D). It is also possible to use liquefied carbon dioxide gas in addition to water.
[0043] In addition to the above, flame retardants, plasticizers, antioxidants, ultraviolet absorbers, colorants, various fillers, internal mold release agents, and other processing aids can be appropriately used. Among these aids, those that do not have active hydrogen groups that can react with isocyanates can be used by mixing them in advance with the isocyanate component.
[0044] The molar ratio (NCO groups / NCO reactive groups) of all isocyanate groups in the polyisocyanate component of the present invention to all isocyanate reactive groups in the isocyanate-reactive compound containing water during mixing and foaming is preferably 0.7 to 1.4 (isocyanate index (NCOINDEX)=70 to 140), and more preferably 0.7 to 1.2 (isocyanate index (NCOINDEX)=70 to 120) as a range that provides good foam durability and molding cycle.
[0045] Next, the method for producing the flexible polyurethane foam of the present invention will be described.
[0046] The method for producing a flexible polyurethane foam of the present invention can use a method for producing a flexible polyurethane molded foam (hereinafter referred to as a "flexible molded foam"), which is characterized in that a foaming liquid mixture of the modified polyisocyanate (C), polyol (D), catalyst, crosslinking agent, foaming agent, and foam stabilizer is injected into a mold, and then foamed and cured.
[0047] The mold temperature when the foaming liquid is injected into the mold is usually 30 to 80° C., preferably 45 to 65° C. If the mold temperature when the foaming liquid is injected into the mold is less than 30° C., the production cycle will be extended due to a decrease in the reaction rate, while if it is higher than 80° C., the reaction between water and isocyanate will be excessively promoted relative to the reaction between polyol and isocyanate, which may cause foam collapse during foaming, deterioration of durability, and adverse effects on the foam's feel.
[0048] The curing time for foaming and curing the foaming liquid is 10 minutes or less, preferably 7 minutes or less, taking into consideration the production cycle of general vehicle seat pads, saddles, and the like.
[0049] When producing the flexible molded foam of the present invention, the above-mentioned components can be mixed using a high-pressure or low-pressure foaming machine, as in the case of ordinary flexible molded foams.
[0050] The polyisocyanate component and the polyol component are preferably mixed immediately before foaming. Other components can be mixed in advance with the polyisocyanate component or the polyol component to the extent that they do not affect the storage stability of the raw materials or the change over time in reactivity. The mixture can be used immediately after mixing, or it can be stored and then used appropriately in the required amount. In the case of a foaming device having a structure capable of simultaneously introducing more than two components into the mixing section, the polyol, foaming agent, polyisocyanate, catalyst, foam stabilizer, additives, etc. can also be introduced into the mixing section individually.
[0051] The mixing method may be either dynamic mixing, in which mixing is performed in the machine head mixing chamber of the foaming machine, or static mixing, in which mixing is performed in the liquid delivery pipe, or both may be used in combination. Mixing of gaseous components such as physical foaming agents with liquid components is often performed by static mixing, while mixing of components that can be stably stored as liquids is often performed by dynamic mixing. The foaming device used in the present invention is preferably a high-pressure foaming device that does not require solvent cleaning of the mixing section.
[0052] The mixture obtained by such mixing is discharged into a metal mold, foamed and cured, and then demolded.
[0053] In order to facilitate the above-mentioned demolding, it is also preferable to apply a mold release agent to the mold in advance. As the release agent, any release agent commonly used in the field of molding can be used.
[0054] The product after demolding can be used as it is, but it is preferable to destroy the cell membrane of the foam under compression or reduced pressure by a conventionally known method to stabilize the subsequent appearance and dimensions of the product.
[0055] As a result, the apparent density according to JIS K6400 is 50kg / m 3 The 25% compression hardness of the skinned foam test piece according to JIS K6400 B method is 100 to 400N / 314cm 2 It is possible to obtain a flexible polyurethane foam having a rebound resilience of 70% or less according to the method described in JIS K6400, a hysteresis loss of less than 30% according to method B of JIS K6400, a dry heat compression set of 4% or less, and a wet heat compression set of 8% or less. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0057] <Synthesis of modified polyisocyanates (I-1~I-9)> In a 1L reactor equipped with a stirrer, thermometer, cooler and nitrogen gas inlet tube, 651.7g of MDI with a total content of 2,2'-MDI and 2,4'-MDI of 55.7% was charged, and the temperature was raised to 75°C. Then, 28.1g of polyol component B-1 (average functionality 2, number average molecular weight 2,000, ethylene oxide unit content 100%, PEG-2000 (trade name) manufactured by Sanyo Chemical Industries) was charged, and the urethane reaction was carried out for 2 hours while uniformly mixing with a stirring blade while maintaining the temperature. Next, 320.2g of polymeric MDI containing 39% MDI with a total content of 2,2'-MDI and 2,4'-MDI of 3.2% was charged, and after stirring for 30 minutes, it was cooled to room temperature to obtain an isocyanate group-terminated prepolymer "I-1" (NCO content 31.7%). Other modified polyisocyanates (I-2 to I-9) were prepared in the same manner as I-1.
[0058] In each example, the composition obtained by adding the MDI (A) charged before the reaction with the polyol component (B) and the polymeric MDI charged after the reaction had an MDI content of 80%, and the total content of 2,2'-MDI and 2,4'-MDI in the MDI was 38.4%.
[0059] <Synthesis of Unmodified Polyisocyanate (I-11, I-12)> In a 1L reactor equipped with a stirrer and nitrogen gas inlet tube, 588.1g of MDI with a total content of 2,2'-MDI and 2,4'-MDI of 55.7% was charged, followed by 411.9g of polymeric MDI containing 39% MDI with a total content of 2,2'-MDI and 2,4'-MDI of 3.2%. After stirring for 30 minutes, unmodified polyisocyanate "I-11" (NCO content 32.5%) was obtained. Other unmodified polyisocyanates (I-12) were also prepared in the same manner as I-11.
[0060] <Preparation of polyol premix> Each raw material was charged in the unit amounts shown in Tables 1 and 2 into a 100 L mixer equipped with an agitator and mixed uniformly.
[0061] [Table 1]
[0062] [Table 2]
[0063] <Raw materials used> Polyol component B-2: polyoxyethylene polyoxypropylene polyol having an average functionality of 4 and a hydroxyl value of 28 (mgKOH / g), QB8000 (product name) manufactured by Toho Chemical Industry Co., Ltd. Polyol component B-3: average functionality 2, number average molecular weight 1,000, ethylene oxide unit content 0%, PP-1000 (product name) manufactured by Sanyo Chemical Industries, Ltd. Polyol component B-4: average functionality 2, number average molecular weight 1,000, ethylene oxide unit content 100%, PEG-1000 (product name) manufactured by Sanyo Chemical Industries, Ltd. Polyol component B-5: average functionality 3, number average molecular weight 7,000, ethylene oxide unit content 70%, FA-159 (product name) manufactured by Sanyo Chemical Industries, Ltd. Polyol component B-6: average functionality 3, number average molecular weight 3,360, ethylene oxide unit content 70%, FA-103 (product name) manufactured by Sanyo Chemical Industries, Ltd. Polyol 1: Polyoxyethylene polyoxypropylene polyol having an average polymerization initiator functionality of 3 and a hydroxyl value of 24 (mgKOH / g), manufactured by AGC, under the trade name of Exenol 851 Polyol 2: Polyoxyethylene polyoxypropylene polyol having an average functionality of 4 and a hydroxyl value of 28 (mgKOH / g), QB8000 (product name) manufactured by Toho Chemical Industry Co., Ltd. Crosslinking agent: Diethanolamine (Mitsui Chemicals) Catalyst 1: 33% dipropylene glycol solution of triethylenediamine, TEDA-L33 (product name) manufactured by Tosoh Corporation Catalyst 2: 70% dipropylene glycol solution of bis(2-dimethylaminoethyl) ether, TOYOCAT-ET (product name) manufactured by Tosoh Corporation Foam stabilizer: Silicone foam stabilizer (manufactured by Evonik, product name: B-8715LF2) Foaming agent: City water.
[0064] <Foam molding> [Foaming conditions] Mold temperature: 55~60℃ ·Mold shape: 100×300×300mm Mold material: Aluminum Cure conditions: 55~60℃ x 5 minutes.
[0065] The liquid temperature of the polyol premix and the polyisocyanates I-1 to I-9 and I-11 was adjusted to 25±1° C. The polyol premix was mixed with the polyisocyanates I-1 to I-9 and I-11 in a ratio that gave the isocyanate index shown in Tables 1 and 2, mixed for 7 seconds with a mixer (7000 rpm), and injected into a mold to foam a flexible foam. The flexible foam was then removed from the mold and broken by roller crushing, after which the physical properties of the resulting flexible foam were measured.
[0066] <Measurement of physical properties of polyurethane foam> The apparent density, rebound resilience, and dry and wet compression set were measured according to the methods specified in JIS K6400, the 25% compression hardness (25% ILD) of the skinned test piece foam was measured according to Method B of JIS K6400, and the hysteresis loss rate was measured according to Method B of JIS K6400.
[0067] <Hysteresis loss rate> If it is below 30%, it is considered good.
[0068] <Rebound elasticity> Anything below 70% is considered good.
[0069] <Dry heat compression residual set> If it is below 4%, it is considered good.
[0070] <Wet and hot compression set> Anything below 8% is considered good.
[0071] <Foam moldability> If the foam does not collapse after foaming and maintains its shape, it is considered to be good (rating: ○).
[0072] <Calculation method for area ratio of urea aggregates and average particle size> The evaluation sample for measuring the area ratio and average particle size of the urea aggregate in the present invention is a central part of 30×50×50 mm of a molded soft polyurethane foam (upper mold side is the lower surface, lower mold side is the upper surface) of 100×300×300 mm. A 3 mm square was cut out from the upper surface side of the evaluation sample, embedded in epoxy resin, cut with a cryomicrotome, and thinned, and measured with a scanning probe microscope (Shimadzu Corporation, SPM-9600) (field of view: 20 μm×20 μm). From the measured phase image, the area of each urea aggregate was calculated using particle analysis software (Shimadzu Corporation, SPM analysis software). The area ratio of the urea aggregates was calculated from the following formula. Area ratio of urea aggregates = total area of each urea aggregate μm 2 / (Cross-sectional area: 400μm 2 )×100...(formula) The average particle size of the urea aggregates was calculated from the following formula. Average particle size of urea aggregates = (average area of urea aggregates / π) 1 / 2 ×2...(formula) *Average area of urea aggregates = area ratio of urea aggregates / number of urea aggregates [Explanation of symbols]
[0073] 1. Urea aggregates
Claims
1. A flexible polyurethane foam comprising urea aggregates, The volume average particle size of the urea aggregate is 0.32 to 0.72 μm; the area ratio of urea aggregates per unit area of the cross section of the flexible polyurethane foam is 6% to 15%; The present invention uses, as isocyanate components, a reaction product of diphenylmethane diisocyanate (A) with a polyol component (B) containing 30 mass% or more of oxyethylene units, and a modified polyisocyanate (C) containing polyphenylene polymethylene polyisocyanate, The modified polyisocyanate (C) has an isocyanate content of 28.1 to 32.4 mass%; A flexible polyurethane foam characterized in that the apparent density is less than 50 kg / m 3 , the 25% compression hardness of a skinned foam test piece is 100 to 400 N / 314 cm 2 , the rebound resilience is 70% or less, the hysteresis loss rate is 30% or less, the dry heat compression set is 4% or less, and the wet heat compression set is 8% or less.
2. 2. The flexible polyurethane foam according to claim 1, wherein the polyol component (B) has a number average molecular weight of 500 to 10,000.
3. 3. The flexible polyurethane foam according to claim 1, wherein the polyol component (B) has an average functionality of 1.7 to 4.3.
Citation Information
Patent Citations
Isocyanate composition and its use in manufacturing expanded polyurethane with improved physico-mechanical characteristics
JP2008179831A
Polyisocyanate composition for flexible polyurethane foam
JP2016033213A
Composition for molding flexible polyurethane form
JP2016060895A
High durability flexible polyurethane foam molding composition
JP2016060896A
Cushioning material
JP2019014848A